Association of Serum Albumin with Short-Term Outcome of Ischemic Stroke (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Serum albumin is proved to be a neuroprotective substance in experimental studies in focal cerebral ischemia.Objective: The aim of this study was to find out any association of serum albumin with the short term outcome of ischemic stroke.Methodology: This observational study was conducted in the Department of Neurology and Department of Internal Medicine at Dhaka Medical College Hospital, Dhaka from January 2011 to December 2011. A total of fifty consecutive patient with first ever ischemic stroke were included. Short term outcome was measured on day 7 using the modified Rankin Scale (mRS) and poor outcome was defined as mRS score 4 to 6 or death. Serum albumin was measured within 24 hours of onset of stroke.Result: Serum albumin was found to be significantly associated with the short-term outcome of ischemic stroke [P-value of Chi square (df = 1) was 0.010]. On logistic regression analysis, SA level [p = 0.018, Odds Ratio (OR) =5.817; 95% confidence interval: 1.348 to 25.106] remained significantly and positively associated with the short-term outcome of ischemic stroke.Conclusion: Serum albumin is significantly associated with the short-term outcome of ischemic stroke and lower level predicts poor outcome and higher level predicts good outcome.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 101-105